2022
DOI: 10.3389/fncel.2022.953534
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microglia phagocytosis and potential involvement of exercise

Abstract: Microglia are considered the main phagocytic cells in the central nervous system, remodeling neural circuits by pruning synapses during development. Microglial phagocytosis is also a crucial process in maintaining adult brain homeostasis and clearing potential toxic factors, which are recognized to be associated with neurodegenerative and neuroinflammatory disorders. For example, microglia can engulf amyloid-β plaques, myelin debris, apoptotic cells, and extracellular harmful substances by expressing a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…However, the effective of IFN-β is dose dependent. Excessive IFN-β responses have harmful effects and facilitate the development of autoimmune diseases ( 112 ). Therefore, proper regulation of the expression and activation of type I IFNs is essential for tissue homeostasis ( 2 ).…”
Section: Commensal Bacteria and Trophoblasts Interactionsmentioning
confidence: 99%
“…However, the effective of IFN-β is dose dependent. Excessive IFN-β responses have harmful effects and facilitate the development of autoimmune diseases ( 112 ). Therefore, proper regulation of the expression and activation of type I IFNs is essential for tissue homeostasis ( 2 ).…”
Section: Commensal Bacteria and Trophoblasts Interactionsmentioning
confidence: 99%
“…We demonstrate here that there is a window during early postnatal life where experience can induce a highly localized increase in the reactivity of microglia to selectively engulf miswired neural projections to drive normative changes. Previous studies have demonstrated that altered experience, including EE, can influence microglial‐engulfment (Augusto‐Oliveira & Verkhratsky, 2021; Li et al, 2022). Much of this work, however, has focused on how experience modulates microglial reactivity as part of the inflammatory response to pathological insult.…”
Section: Discussionmentioning
confidence: 99%
“…The putamen is a common site for synaptic pruning, and depression was reported to disrupt such a process [ 80 , 81 ]. We speculate that the reduced putamen volume found in the Tai Chi training group could have been due to the post-intervention effect on restoring the pruning process [ 82 ]. Future study is to gather additional evidence to support our speculation.…”
Section: Discussionmentioning
confidence: 99%